Internationalization concept: Integrating a global perspective in UCN - de Brito Silva, Priscila; Hansen, Lise Eckardt; Drachmann, Dorte (UCN Perspektiv, 2020)
Starting from the first semester, UCN is taking initiatives to progressively implement the concept of internationalization at home (IaH) throughout the course of its physiotherapy programme. The initiatives include research and development activities as well as competency development, thus offering students and staff unique opportunities to interact with international peers. This article aims at describing these IaH implementation initiatives and to show how lecturers, clinical supervisors and students perceive the impact of international strategies on our students’ professional and personal development. We interviewed staff and students who had been in contact with international students in Denmark. In general, lecturers and clinical supervisors report that the IaH initiatives have had a positive impact on local students, emphasizing that they need to be well-prepared before embarking on an exchange period. The students explained how valuable internationalization had been to their professional development and suggested that IaH initiatives could broaden local students’ participation in international exchange experiences.